2017
DOI: 10.1002/acr.22925
|View full text |Cite
|
Sign up to set email alerts
|

Heart Disease, Hypertension, Gestational Diabetes Mellitus, and Preeclampsia/Eclampsia in Mothers With Juvenile Arthritis: A Nested Case–Control Study

Abstract: Women with a history of juvenile arthritis had a higher risk of heart disease. This risk signals the potential importance of cardiac prevention strategies in juvenile arthritis. As this was a retrospective study, it was not possible to correct for some relevant potential confounders. Further studies should assess the impact of medications, disease severity, and other factors (e.g., obesity) on cardiac outcomes in juvenile arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Even though most authors describe an increased risk of pre-eclampsia in JIA pregnancies compared to the general population, our observation has been reported also by others. 2,5,6,9,27 Caesarean section was very common in our JIA patients, with a probability of 67.6%. This figure was significantly higher than both healthy and disease controls, and might be partially explained by concerns about parturition stress on hip prosthesis.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Even though most authors describe an increased risk of pre-eclampsia in JIA pregnancies compared to the general population, our observation has been reported also by others. 2,5,6,9,27 Caesarean section was very common in our JIA patients, with a probability of 67.6%. This figure was significantly higher than both healthy and disease controls, and might be partially explained by concerns about parturition stress on hip prosthesis.…”
Section: Discussionmentioning
confidence: 75%
“…Even though most authors describe an increased risk of pre-eclampsia in JIA pregnancies compared to the general population, our observation has been reported also by others. 2 , 5 , 6 , 9 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potentially influential role of education is important given our respondents' desire to learn more about specific topics and their lack of confidence in existing privacy and security procedures. To address these needs, we recommend showcasing Canadian studies in which administrative data were used to assess complications [40][41][42] and long-term effects [43][44][45][46] of medications in patients with chronic diseases. Furthermore, it is essential to provide more information about the role of data stewards in adjudicating data requests and imposing conditions to data access.…”
Section: Discussionmentioning
confidence: 99%
“…prevalence of metabolic syndrome is increased in adults with a history of arthritis (6). A study of women of childbearing potential showed that women with a history of arthritis had a higher risk of heart disease compared to those without arthritis (13). To our knowledge, our study is the first to evaluate the risk of CAD in adults with a history of JA regardless of sex or race.…”
Section: Discussionmentioning
confidence: 80%